Środowisko – tak. Zieloni – nie. Problematyka ochrony środowiska naturalnego w badaniach empirycznych - Czaja, Marek; Gutowski, Szymon (Political Preferences, 2014)
This article presents the perception of environmental issue by Polish society - attaching importance to these issues and the assessment of political activities in solving environmental problems. The first part of the article describes environmentalism and the green parties which gained relevant position in Western European party system in the 70s of the twentieth century. Then the activities of the Greens in Poland and other Central European countries are described that took place after the collapse of the communist system in 1989. The article also illustrates the results of research on social perception of the environmental issues. The vast majority of Poles consider these issues important and claim that politicians should increase their activities in this area. Nevertheless, this doesn't affect the position of the Greens in the Polish party system. This is due to the history after World War II when Central Europe was in the Soviet sphere of influence and the weakness of the green parties that have never been able to present their offer efficiently to public opinion.